Loss of function mutations in GEMIN5 cause a neurodevelopmental disorder - Sukhleen Kour (Nature Portfolio, 2021)
GEMIN5, an RNA-binding protein, is required for formation of small nuclear ribonucleoproteins. Here, the authors identify loss of function mutations in GEMIN5 that are associated with a human neurodevelopmental disorder.